2021
DOI: 10.1155/2021/2508780
|View full text |Cite
|
Sign up to set email alerts
|

The Probable Association between Chronic Toxoplasma gondii Infection and Type 1 and Type 2 Diabetes Mellitus: A Case-Control Study

Abstract: Purpose. The probable association between Toxoplasma gondii (T. gondii) infection and diabetes mellitus (DM) is still controversial, and there are several studies with conflicting results. Thus, this study was performed to assess the possible association between chronic T. gondii infection and type 1 diabetes mellitus (T1DM) and T2DM. Methods. In this case-control study, a total of 105 diabetic subjects including 36 patients with T1DM and 69 patients with T2DM were recruited. In addition, 150 nondiabetic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…According to the results, there was only a statistically significant difference between contact with cats and IgG seroprevalence. This study confirmed some previous reports highlighting the importance of cats in acquiring T. gondii infection (6,7,11). In conclusion, the present study revealed a relatively high seroprevalence of T. gondii infection among T1DM patients in Abadan, southwest Iran.…”
Section: Dear Editorsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the results, there was only a statistically significant difference between contact with cats and IgG seroprevalence. This study confirmed some previous reports highlighting the importance of cats in acquiring T. gondii infection (6,7,11). In conclusion, the present study revealed a relatively high seroprevalence of T. gondii infection among T1DM patients in Abadan, southwest Iran.…”
Section: Dear Editorsupporting
confidence: 92%
“…The results of the present study demonstrated that 28 subjects (68.29%) were seropositive. In accordance with our results, Soltani et al reported that the seroprevalence of T. gondii infection in T1DM patients was 69.4% in Khorramshahr, southwest Iran (6). In addition, Nassief Beshay et al reported 86.37% seropositivity rate of anti-T. gondii IgG among T1DM patients (10).…”
Section: Dear Editorsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the main risk factor for T. gondii IgG seroprevalence in patients with T2DM and without DM was contact with cats. 63 Another recent study conducted by Al-Khafajii et al 64 assessed toxoplasmosis positivity in relation to BMI in patients with diabetes and metabolic syndrome, including obesity, overweight, normal weight, diabetes, non-diabetes, obesity-diabetes, obesity-non-diabetes, overweight-diabetes, overweight-non-diabetes, and normal weight-non-diabetes, and found that the rate of T. gondii seropositivity showed no significant difference among the study groups. Indeed, it is necessary to expand and develop experimental and human studies on T. gondii infection under the conditions of DM and obesity to identify other variables that can induce favorable or harmful events.…”
Section: Metabolic Diseases Associated With Protozoan Infectionsmentioning
confidence: 99%
“…In addition, the main risk factor for T. gondii IgG seroprevalence in patients with T2DM and without DM was contact with cats. 63…”
Section: Metabolic and Parasitic Diseasesmentioning
confidence: 99%